Phototherapy as a First Line Treatment for Mycosis Fungoides: A 10-year Retrospective Study - Alexandra Azevedo; Iolanda Fernandes; Renata Cabral; Margarida Lima; Isabel Amorim; Manuela Selores (Sociedade Portuguesa de Dermatologia e Venereologia, 2019)
Introduction: Phototherapy, particularly psoralen plus ultraviolet A (PUVA) and narrowband ultraviolet B (nbUVB), is a mainstay in the treatment of Mycosis Fungoides (MF). Methods: We analyzed outcomes of MF patients treated for the first time with either PUVA or nbUVB at the Photodermatology Unit, in the Department of Dermatology of Centro Hospitalar Universitário do Porto, from 2007 to 2017. The primary outcome was response to treatment. The secondary outcome was disease relapse free survival. Results: From a total number of 34 patients with MF identified, nine (26.5%) patients were diagnosed at stage IA and 25 (73.5%) patients were diagnosed at stage IB. Of these patients, 30 (88.2%) were treated with PUVA and four (11.8%) with nbUVB. Overall, 24 (80%) patients treated with PUVA and two (50%) patients treated with nbUVB had complete responses (CR). Relapse was observed in 17 (70.8%) PUVA treated patients and two (100%) nbUVB treated patients. Median disease relapse free survival was 12 months for PUVA and 6 months for nbUVB. Conclusion: PUVA is an effective therapy in early MF. Narrowband UVB could be a valid therapeutic alternative for these patients. However, the small size of nbUVB group in our study limits the conclusions about its efficacy.